2018
DOI: 10.1002/pca.2805
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic study of bioactive compounds in strawberries preserved under controlled atmosphere based on GC‐MS and DI‐ESI‐QqQ‐TOF‐MS

Abstract: Introduction The storage of the vegetables products in a controlled atmosphere (CA) with low O2 and high CO2 concentrations, reduces respiration rates and delays the ripening process, and in some cases, improves their quality and organoleptic properties. Objective To obtain deep insight into strawberry fruit metabolic changes caused by these CA treatments. Methodology Freshly harvested strawberries were preserved under different atmospheres enriched with 10%, 20% and 30% of CO2, for 2 days at 0°C, containing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The hardness of the apple pulp was determined by an FT -372 penetrometer with a plunger with a diameter of 11 mm; tasting evaluation -according to GOST 8756.1-79 [28]; the chemical composition of apples was determined by methods generally accepted in fruit biochemistry: soluble dry substances -by the refractometric method (GOST 28562-90) [29]; sugars -by the Bertrand spectrophotometric method (GOST 8756. 13…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hardness of the apple pulp was determined by an FT -372 penetrometer with a plunger with a diameter of 11 mm; tasting evaluation -according to GOST 8756.1-79 [28]; the chemical composition of apples was determined by methods generally accepted in fruit biochemistry: soluble dry substances -by the refractometric method (GOST 28562-90) [29]; sugars -by the Bertrand spectrophotometric method (GOST 8756. 13…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…However, such storage does not replace storage in the refrigerator (its temperature is usually 3 -5 °C higher than in the refrigerator). The storage of fruit products in the CA slows down the processes of maturation and overripe, as a result of which its shelf life is lengthened, the quality and yield of marketable products are increased, immunity is preserved, microbial spoilage and physiological damage are reduced [12], [13], [14]. Biological oxidation (respiratory gas exchange or respiratory activity) is at the center of physiological and biochemical processes during fruit ripening.…”
Section: Introductionmentioning
confidence: 99%
“…Ramírez‐Acosta et al . (2019) identified GCMS and DIESIQqQTOFMS as appropriate and complementing metabolomic methods for characterising the metabolic changes in strawberry caused by controlled atmosphere storage. They reported changes in primary and secondary metabolites including organic acids, sugars and phenolic compounds.…”
Section: Fruits Metabolomicsmentioning
confidence: 99%
“…76 Ramírez-Acosta, S. et al used GC-MS technology to study the metabolic changes of strawberry fruit caused by controlled atmosphere treatment, and found that several metabolites related to it were mainly biologically active compounds. 77 Kim, G. D. et al used LC-MS/MS to identify caffeic acid derivatives and Danshensu as the main anti-inammatory substances in the leaves of kiwi fruit plants. 78 However, it is not only vegetables and fruits that provide nutrients, and many other substances provide essential proteins, lipids and sugars to the body.…”
Section: Nutritionmentioning
confidence: 99%